Biodegradação de Hidrocarbonetos Aromáticos Policíclicos - Jacques, Rodrigo Josemar Seminoti (2007)
Polycyclic aromatic hydrocarbons (PAHs) are not degraded bymost of the microorganisms, due to the complexity of its chemical structureand low solubility in water. In spite of that, these compounds are generatedin petrochemical activities, with high potential for contamination of thenatural ecosystems. PAHs and its derivatives are know mutagenic andcarcinogenic compounds, being associated to the increase of cancerincidence in the lung, intestine, liver, and pancreas and in the humans' skinand animals. The use of microbial degraders is an alternative for PAHselimination to the atmosphere. Besides the selection of the microorganismswith proven capacity of degradation of these compounds, it is necessaryappropriate conditions for biodegradation as available water, inorganicnutrition, adequate pH and temperature, as well to increase PAHsbioavailability in soil due to strong tendency of sorption to minerals andorganics particules of soils and sediments. The objective of this revisionwas to discuss PAHs environmental behavior, microbial metabolism of thesecompounds and the environmental factors that influence the survival andthe activity of the PAHs microbial degrader community.